Comparative Study of the Incorporation of Gold and Silver Nanoparticles into N-719 Dye on the Performance of Dye-Sensitized Solar Cell (DSSC) - Hawinda Restu Putri; Hilarius Donatus Hun; Setiya Rahayu; Herman; Muhammad Tegar Pambudi; Priastuti Wulandari (Program Studi Fisika Universitas Negeri Jakarta, 2025)
The Dye-Sensitized Solar Cell (DSSC) is a promising third-generation solar cell technology with very significant enhancement in device efficiency. The modification in the fabrication of DSSC is still being studied today in order to increase the stability and lifetime of the devices. The aims of our research is to compare the incorporation of gold and silver nanoparticles capped with 3-Mercaptopropionic Acid (AuMPA or AgMPA) into N-719 dye to enhance DSSC performance. Metal nanoparticles exhibit a unique optical property called Localized Surface Plasmon Resonance (LSPR), which maximizes light absorption. In our experiment, AuMPA and AgMPA were prepared using the chemical reduction method and then incorporated into the dye solution and then in the DSSC assemble, the electrode-TiO2 layer were immersed into dye contained NPs solution. Optical characterization, including absorbance and photolumine-scence spectra, shows a blue shift in the spectral position and an overlap between the intrinsic peak of N-719 and the plasmonic peak of AuMPA or AgMPA, indicating a stable nanoparticle dispersion within the dye matrix. Fourier Transform Infrared (FTIR) spectra confirm the chemical interaction through the changes in the S-H and -COOH vibrations. Scanning Electron Microscopy (SEM) observation reveals the presence and growth of AuMPA and AgMPA nanoparticles within the mesoporous TiO2 layer. The addition of AuMPA into the dye solution increases the PCE of the device from 3.32% to 4.19%, while AgMPA yielded a PCE of 3.76%. Enhancement of our DSSC performance is attributed to the LSPR effect, which enhances light absorption and charge transport. The better performance by the addition of AuMPA into the dye is attributed to a highly substantial plasmonic effect and stability, while AgMPA tends to aggregate, limiting its effectiveness.